FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Orang Pribadi di KPP Pratama Semarang Tengah Satu dan KPP Pratama Semarang Tengah Dua) - Nur Lita, 13.05.52.0034; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of e-Filing system Implementation, Taxpayer Awareness and Internet Understanding of Taxpayer Compliance on Individual Taxpayerin KPP Pratama Semarang Tengah Satu and KPP Pratama Semarang Tengah Dua. This research data is obtained from questionnaires distributed to Taxpayers registered in KPP Pratama Semarang Tengah Satu and KPP Pratama Semarang Tengah Dua. The population of this study are individual Texpayer registered in KPPÂ Pratama Semarang Tengah Satu and KPP Pratama Semarang Tengah Dua. Sampling method used in Conveniance Sampling. The analysis method of this research is multiple linier regression method. This results of this study indicate that the implementation of e-Filing System has a positive ang not significant impact on Taxpayer Compliance, Taxpayer Awareness has a positive and not significant impact on taxpayer compliance, Internet Understanding has a negative and not significant effect on Taxpayer Compliance.Keywords: Implementation of e-Filing System, Taxpayer Awareness, Internet Understanding, Taxpayer Compliance